The influence of knowledge and group therapy on postpartum blues at PMB Bangsalan Teras Boyolali - Ernawati, Ernawati; Widyastuti, Deny Eka; Umarianti, Tresia; Rohmatika, Dheny; Apriani, Arista; Rahardjoputro, Rolando (International Journal of Health Science and Technology, 2024)
During the birth period, sometimes support from the family is needed. This kind of situation can be a trigger that causes depression in postpartum mothers. Depression felt by the individual can cause an attempt to react to the depression experienced. This reaction is an activity to make adjustments to certain stimulus situations, which if not done properly will cause physical and psychological disorders. Symptoms arising from postpartum depression are filled with feelings and depression accompanied by crying for no reason, having no energy or only a little energy they have, unable to concentrate, feeling guilty and worthless in themselves, becoming uninterested in babies. For mothers who suffer from postpartum depression, they cannot establish a good relationship with their newborn baby. Group therapy to reduce depression includes psychoeducation groups, supportive groups, and self-help groups. The purpose of this study is to analyze the provision of self-help group therapy to mothers with postpartum depression. The research design uses an experimental quasy with one group pretest-posttest. The results showed that there was a significant relationship between knowledge and the incidence of postpartum blues, with a p-value of 0.001. The provision of